2012
DOI: 10.4103/1817-1737.102166
|View full text |Cite
|
Sign up to set email alerts
|

The Saudi initiative for asthma - 2012 update: Guidelines for the diagnosis and management of asthma in adults and children

Abstract: This an updated guidelines for the diagnosis and management of asthma, developed by the Saudi Initiative for Asthma (SINA) group, a subsidiary of the Saudi Thoracic Society. The main objective of SINA is to have updated guidelines, which are simple to understand and easy to use by non-asthma specialists, including primary care and general practice physicians. This new version includes updates of acute and chronic asthma management, with more emphasis on the use of Asthma Control Test in the management of asthm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(55 citation statements)
references
References 200 publications
(249 reference statements)
0
55
0
Order By: Relevance
“…Although there have been a few studies on the prevalence of asthma in some cities in Saudi Arabia, there is no official information regarding the prevalence of asthma throughout the whole country (i.e., there is no national dataset for asthma prevalence). However, in 2012, the Saudi Initiative for Asthma (SINA) reported that more than two million Saudis have asthma (Al Frayh et al 2001;Al-Moamary et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been a few studies on the prevalence of asthma in some cities in Saudi Arabia, there is no official information regarding the prevalence of asthma throughout the whole country (i.e., there is no national dataset for asthma prevalence). However, in 2012, the Saudi Initiative for Asthma (SINA) reported that more than two million Saudis have asthma (Al Frayh et al 2001;Al-Moamary et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Male to female ratio is found 1. 11 and Yooet al 10 have also observed male predominant in their studies, where they have found that 53.8% and 53.7% are male respectively.In this series it has been observed that majority (78.0%) patients have positive family history of asthma. Similarly, Bandyopadhyayet al 13 and Khakzadet al 8 have showed that family history of Asthma are 47.5% and 43.0% respectivelywhich are comparable with the current study.…”
Section: Discussionmentioning
confidence: 82%
“…Yooet al10have showed the mean (±SD) age was found 11.4±2.2 years, which is lesser with the current study. On the other hand Al-Moamaryet al 11 have found that the mean age is 32.05±10.87 years. The higher mean age and age range has obtained by the above authors whichmaybe due to geographical variation as well as racial influences.In this study it has been observed that cough-variant-asthma is predominant in male subject where 58.0% patients are male and 42.0% populations are female.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yoo et al 13 have showed that the mean (±SD) age is 11.4±2.2 years, which is lesser with the present study. On the other hand Al-Moamary et al 14 have found that the mean age is 32.05±10.87 years. The high mean age and age range has been obtained may be due to geographical variation as well as racial influences.…”
Section: Sputum Eosinophilmentioning
confidence: 90%